2017
DOI: 10.1115/1.4037644
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Flow Boiling Using Radial Open Microchannels With Manifold and Offset Strip Fins

Abstract: The increasing demand for designing effective cooling solutions in high power density electronic components has resulted in exploring advanced thermal management strategies. Over the past decade, phase-change cooling has received widespread recognition due to its ability to dissipate large heat fluxes while maintaining low temperature differences. In this paper, a radial flow boiling configuration through a central inlet was studied. This configuration is particularly suited for chip cooling application. Two h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Further, high-speed visualization was performed to better understand bubble dynamics for the radial geometry. Further extending the work, Alyssa et al 19 fabricated an offset strip fin radial microchannel to compare its thermal performance with a radial straight microchannel (RSMC). Their study demonstrated the potential of removing heat fluxes as high as 618 W/cm 2 at the wall superheating of 20 °C using offset strip fins when compared to a heat flux of 396 W/cm 2 that is removed by radial straight channels for the same mass flow rate of 240 ml/min.…”
Section: Introductionmentioning
confidence: 99%
“…Further, high-speed visualization was performed to better understand bubble dynamics for the radial geometry. Further extending the work, Alyssa et al 19 fabricated an offset strip fin radial microchannel to compare its thermal performance with a radial straight microchannel (RSMC). Their study demonstrated the potential of removing heat fluxes as high as 618 W/cm 2 at the wall superheating of 20 °C using offset strip fins when compared to a heat flux of 396 W/cm 2 that is removed by radial straight channels for the same mass flow rate of 240 ml/min.…”
Section: Introductionmentioning
confidence: 99%
“…Conventional cooling methods, such as air cooling through fans or pumped liquid cooling, cannot cope with such high heat dissipation demands. Flow boiling heat transfer within microchannels has been recognised experimentally as one of the most efficient thermal management solutions for such high-power density electronic components, dissipating heat fluxes in the order of MW/m 2 [2], [3]. However, cooling of micro-electronics utilising flow boiling within micro-passages is not yet commercially available and it is still limited to laboratory applications.…”
Section: Introductionmentioning
confidence: 99%
“…In recent studies, heat sinks have exhibited high heat transfer performance. Recinella and Kandlikar (2018) achieved a heat flux of 6.18×10 6 W/m 2 at a wall superheat of 20.1 K and a pressure drop of 13.8 kPa with distilled water using radial open microchannels with a manifold and offset strip fins. Shultz et al (2015) achieved a heat flux of approximately 3.5×10 6 W/m 2 with a flow rate of 4.2×10 -3 kg/s and a stable pressure drop of 320 kPa with a radial array of channels using the dielectric coolant R1234ze(E).…”
Section: Introductionmentioning
confidence: 99%